Ternary high-nickel positive electrode material and preparation method thereof, lithium ion battery and electric equipment
By using wet water washing coating technology and multiple sintering treatments in the ternary high-nickel cathode material, a uniform needle-shaped coating layer is formed, which solves the cation mixing problem caused by nickel ion activity and improves the performance and life of the battery.
Patent Information
- Application Number
- CN202510200205.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The high activity of nickel ions in the ternary positive electrode material leads to cation mixing and dissipation, resulting in battery capacity decay, rate performance, cycle performance and thermal stability performance degrade, limiting the application of materials in the fields of high-performance and long-life batteries.
A method of preparing a ternary high nickel positive electrode material is adopted. By mixing the positive electrode material precursor, lithium source, and zirconium-containing and titanium-containing additives, it is then subjected to wet water washing and coating, and finally three sintering with the doping element-containing additives to form a uniform needle-like cladding layer.
It effectively prevents direct contact between the electrolyte and the material, reduces the occurrence of side reactions, avoids the migration of lithium ions to the surface, maintains the structural stability of the material, is conducive to the utilization of capacity, improves the uniformity and consistency of the coating, and extends the service life of the battery.
Smart Images

Figure CN119660829A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a ternary high-nickel positive electrode material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art
[0002] With its high gram capacity, high energy density and environmentally friendly characteristics, ternary cathode materials have become an indispensable portable energy solution in modern life and are playing an increasingly important role in industrial production. With the rapid development of electric vehicles, energy storage systems and portable electronic devices, the market's requirements for battery performance are constantly increasing, which has driven the development of ternary cathode materials towards higher nickel content. High nickel content can not only further improve the energy density of the battery, but also reduce costs, which is an important way to achieve battery performance optimization.
[0003] However, as the nickel content increases, ternary cathode materials face a series of new challenges. The high activity of nickel ions leads to cation mixing, especially the mixing of nickel ions and lithium ions, which not only leads to the decline of battery capacity, but also significantly reduces the rate performance, cycle performance and thermal stability of the material. These negative effects greatly shorten the service life of lithium batteries and limit the application of ternary cathode materials in the field of high-performance and long-life batteries.
[0004] In order to overcome these challenges, researchers have conducted extensive modification research on ternary cathode materials, among which doping and coating are the two main modification methods. However, the traditional dry coating process has the problem of uneven coating, resulting in poor overall coating effect of the material and failure to fully exert the protective effect of the coating layer.
[0005] Although the wet coating process improves the uniformity of coating to a certain extent, lithium ions are prone to migrate to the surface during the preparation process, which not only destroys the internal structure of the material but also affects the electrochemical performance of the battery. Summary of the invention
[0006] The purpose of this application is to provide a ternary high-nickel positive electrode material and a preparation method thereof, a lithium-ion battery and an electrical device to solve the above-mentioned problems.
[0007] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a ternary high-nickel positive electrode material, comprising: The positive electrode material precursor, the lithium source and the zirconium-containing additive are mixed and sintered once to obtain a sintered product; The primary sintered product is mixed with a titanium-containing additive and subjected to secondary sintering to obtain a secondary sintered product; The secondary sintered product is mixed with water and aluminum nitrate, subjected to wet washing and coating, filtered, and dried to obtain a coated material; The coated material is mixed with an additive containing a doping element and sintered three times to obtain a ternary high-nickel positive electrode material, wherein the doping element includes at least one of B, Mg, Y, and Mo.
[0008] According to an embodiment of the present application, the positive electrode material precursor includes Ni x Co y Mn z (OH)2, where, x≥0.9, y>0, z>0, x+y+z=1; And / or, the lithium source comprises lithium hydroxide; And / or, the molar ratio of lithium in the lithium source to the total content of nickel, cobalt and manganese in the positive electrode material precursor is 1:(1-2); and / or, the zirconium-containing additive comprises zirconium oxide; and / or, the mass of the zirconium-containing additive is 0.1wt%-0.3wt% of the mass of the positive electrode material precursor; and / or, the sintering atmosphere of the primary sintering includes oxygen; And / or, the heating rate of the primary sintering is 1-5°C / min; And / or, the primary sintering temperature is 700-1000°C; And / or, the time of the primary sintering is 12-14 hours.
[0009] According to an embodiment of the present application, the titanium-containing additive includes at least one of tetra-tert-butyl titanate, alkoxy titanate, and tetrabutyl titanate; and / or, the mass of the titanium-containing additive accounts for 0.1wt%-1wt% of the mass of the product after the primary sintering; and / or, the sintering atmosphere of the secondary sintering includes oxygen; And / or, the heating rate of the secondary sintering is 1-5°C / min; And / or, the secondary sintering temperature is 400-800°C; And / or, the secondary sintering time is 9-12 hours.
[0010] According to an embodiment of the present application, the mass of the aluminum nitrate accounts for 1.2wt%-2.4wt% of the mass of the product after the secondary sintering.
[0011] According to an embodiment of the present application, the mixing of the secondary sintered product with water and aluminum nitrate comprises: first mixing the secondary sintered product with water, and then adding an aluminum nitrate solution, wherein the aluminum nitrate solution is prepared by mixing aluminum nitrate with water; The mass ratio of the secondary sintered product to water is 1:(1-1.8); The mass ratio of the secondary sintered product to the aluminum nitrate solution is 1:(2.012-2.024); The mass fraction of aluminum nitrate in the aluminum nitrate solution is 0.60%-1.19%.
[0012] According to an embodiment of the present application, the drying is performed under vacuum conditions, and the drying temperature is 100-160° C.; And / or, the drying time is 2-4 hours.
[0013] According to an embodiment of the present application, the doping element-containing additive includes boric acid; and / or, the mass of the additive containing the doping element accounts for 0.05wt%-0.2wt% of the mass of the coated material; and / or, the sintering atmosphere of the third sintering includes oxygen; And / or, the heating rate of the three sinterings is 1-5°C / min; And / or, the temperature of the three sinterings is 200-400°C; And / or, the time of the three sinterings is 9-12 hours.
[0014] The present application also provides a ternary high-nickel positive electrode material, which is prepared by the preparation method of the ternary high-nickel positive electrode material described above.
[0015] The present application also provides a lithium-ion battery, which includes a ternary high-nickel positive electrode material prepared by the preparation method of the ternary high-nickel positive electrode material described above or includes the ternary high-nickel positive electrode material described above.
[0016] The present application also provides an electrical device, which includes the lithium-ion battery described above.
[0017] Compared with the prior art, the beneficial effects of this application include: The present application proposes a method for preparing a ternary high-nickel positive electrode material. Through wet water washing and coating, a uniform needle-shaped coating layer can be formed on the surface of the product after secondary sintering. This coating layer can not only effectively prevent direct contact between the electrolyte and the material and reduce the occurrence of side reactions, but also avoid the migration of lithium ions to the surface, thereby maintaining the structural stability of the material and facilitating the use of capacity. Compared with the traditional wet coating process, the method of the present application solves the problem of lithium ion migration; compared with the dry coating process, the uniformity and consistency of the coating are greatly improved. In general, the positive electrode material prepared by the present application can avoid the migration of lithium ions to the surface while ensuring the uniformity of the coating. Moreover, the method of the present application also has the advantage of simple operation, which is conducive to large-scale promotion and application.
[0018] The ternary positive electrode material prepared in the present application not only has a higher discharge capacity, but also maintains a lower residual alkali content, thereby improving battery performance while extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0020] Figure 1 is a SEM image of the material after primary sintering and pulverization in Example 2; Figure 2 is a SEM image of the material with a needle-shaped surface coating layer after wet washing and coating in Example 2; Figure 3 are SEM images of the material with a needle-shaped surface coating layer after wet washing and coating in Example 2 at different magnifications; Figure 4 is a coating element distribution diagram of the material with a needle-shaped surface coating layer after wet washing and coating in Example 2; Figure 5 This is a SEM image of the ternary high-nickel positive electrode material prepared in Example 2. DETAILED DESCRIPTION
[0021] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0022] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0023] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0024] In these examples, parts and percentages are by mass unless otherwise indicated.
[0025] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0026] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0027] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows: A method for preparing a ternary high-nickel positive electrode material, comprising: The positive electrode material precursor, the lithium source and the zirconium-containing additive are mixed and sintered once to obtain a sintered product; The primary sintered product is mixed with a titanium-containing additive and subjected to secondary sintering to obtain a secondary sintered product; The secondary sintered product is mixed with water and aluminum nitrate, subjected to wet washing and coating, filtered, and dried to obtain a coated material; The coated material is mixed with an additive containing a doping element and sintered three times to obtain a ternary high-nickel positive electrode material, wherein the doping element includes at least one of B, Mg, Y, and Mo.
[0028] The present application can effectively remove excess residual alkali on the surface of the material through wet water washing coating, improve the processing performance of the material, and form an aluminum nitrate coating layer, which can effectively improve the performance of the positive electrode material.
[0029] According to an embodiment of the present application, the positive electrode material precursor includes Ni x Co y Mn z (OH)2, wherein x≥0.9, y>0, z>0, and x+y+z=1; for example, x may be 0.9, y may be 0.06, and z may be 0.04.
[0030] The cathode material precursor includes but is not limited to Ni 0.9 Co 0.06 Mn 0.04 (OH)2.
[0031] And / or, the lithium source comprises lithium hydroxide; And / or, the molar ratio of lithium in the lithium source to the total content of nickel, cobalt and manganese in the positive electrode material precursor is 1:(1-2); For example, the molar ratio of lithium in the lithium source to the total content of nickel, cobalt and manganese in the positive electrode material precursor can be 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9, 1:1.95, 1:2 or any value between 1:(1-2).
[0032] And / or, the zirconium-containing additive includes zirconium oxide; the addition of zirconium oxide can improve the stability of the positive electrode material, thereby increasing the cycle life of the positive electrode material, and the addition of zirconium oxide can improve the conductivity of the positive electrode material, thereby improving the charge and discharge efficiency of the positive electrode material.
[0033] And / or, the mass of the zirconium-containing additive is 0.1wt%-0.3wt% of the mass of the positive electrode material precursor; if the content of the zirconium-containing additive is too low, the effect of stabilizing the structure and improving the cycle life cannot be achieved; if the content of the zirconium-containing additive is too high, the transmission effect of lithium ions will be affected.
[0034] For example, the mass of the zirconium-containing additive may be 0.1 wt%, 0.2 wt%, 0.3 wt% or any value between 0.1 wt% and 0.3 wt% of the mass of the positive electrode material precursor.
[0035] In some embodiments, the mixing of the positive electrode material precursor, the lithium source, and the zirconium-containing additive is carried out in a high-speed mixer, and the high-speed mixer can be mixed at a low speed, and then mixed at a high speed to achieve uniform mixing of the positive electrode material precursor, the lithium source, and the zirconium-containing additive. For example, the low speed of the high-speed mixer can be 100-300r / min, preferably 270r / min; the mixing time of the high-speed mixer at the low speed can be 1-10min, preferably 5min; the high-speed speed of the high-speed mixer can be 400-800r / min, preferably 500r / min; the mixing time of the high-speed mixer at the high speed can be 10-30min, preferably 20min.
[0036] and / or, the sintering atmosphere of the primary sintering includes oxygen; And / or, the heating rate of the primary sintering is 1-5°C / min; For example, the heating rate of the primary sintering may be 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, or any value between 1° C. / min and 5° C. / min.
[0037] And / or, the primary sintering temperature is 700-1000°C; For example, the primary sintering temperature may be 700°C, 800°C, 900°C, 1000°C or any value between 700-1000°C.
[0038] And / or, the time of the primary sintering is 12-14 hours.
[0039] For example, the time for one sintering can be 12 hours, 13 hours, 14 hours or any value between 12 and 14 hours.
[0040] According to an embodiment of the present application, after the primary sintering is completed, the method further includes: pulverizing the physical after the primary sintering is completed to obtain a primary sintered product; specifically, a mechanical pulverizer can be used to pulverize the physical after the primary sintering to make the D50 of the primary sintered product between 8.5-11.5 μm; According to an embodiment of the present application, the titanium-containing additive includes at least one of tetra-tert-butyl titanate, alkoxy titanate, and tetrabutyl titanate; by adding the titanium-containing additive, the crystal structure stability of the positive electrode material can be improved, thereby improving the cycle and rate performance of the material.
[0041] and / or, the mass of the titanium-containing additive accounts for 0.1wt%-1wt% of the mass of the product after the primary sintering; For example, the mass of the titanium-containing additive may account for 0.1 wt%, 0.5 wt%, 1 wt% or any value between 0.1 wt% and 1 wt% of the mass of the product after the primary sintering.
[0042] According to an embodiment of the present application, the mixing of the primary sintered product and the titanium-containing additive is carried out in a high-speed mixer. When the primary sintered product is mixed with the titanium-containing additive, the method further comprises adding ethanol. Specifically, the titanium-containing additive can be mixed with ethanol to prepare a titanium-containing additive solution, and then the titanium-containing additive solution is sprayed on the primary sintered product placed in the high-speed mixer. The pressure of the titanium-containing additive solution spraying can be 0.05-0.2MPa.
[0043] and / or, the sintering atmosphere of the secondary sintering includes oxygen; And / or, the heating rate of the secondary sintering is 1-5°C / min; For example, the heating rate of the secondary sintering may be 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, or any value between 1° C. / min and 5° C. / min.
[0044] And / or, the secondary sintering temperature is 400-800°C; For example, the secondary sintering temperature may be 400°C, 500°C, 600°C, 700°C, 800°C or any value between 400-800°C.
[0045] And / or, the secondary sintering time is 9-12 hours.
[0046] For example, the secondary sintering time may be 9 hours, 10 hours, 11 hours, 12 hours or any value between 9 and 12 hours.
[0047] According to the embodiments of the present application, the mass of the aluminum nitrate accounts for 1.2wt%-2.4wt% of the mass of the product after the secondary sintering. The addition of aluminum nitrate can form a needle-shaped Al(NO3)3 coating layer evenly on the surface of the material, which can reduce surface impedance, improve cycle stability and increase capacity retention. If the mass of aluminum nitrate is too low, it will not achieve a significant effect of improving performance; if the mass of aluminum nitrate is too much, it will cause adverse effects such as low capacity.
[0048] For example, the mass of aluminum nitrate can account for 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt% or any value between 1.2wt% and 2.4wt% of the mass of the product after secondary sintering.
[0049] According to an embodiment of the present application, the mixing of the secondary sintered product with water and aluminum nitrate comprises: first mixing the secondary sintered product with water, and then adding an aluminum nitrate solution, wherein the aluminum nitrate solution is prepared by mixing aluminum nitrate with water; In some embodiments, the secondary sintering product is mixed with water and aluminum nitrate under stirring conditions. The stirring speed may be 200-800 r / min, and the adding speed of the aluminum nitrate solution may be 30-80 ml / min.
[0050] The mass ratio of the secondary sintered product to water is 1:(1-1.8). For example, the mass ratio of the secondary sintered product to water can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8 or any value between 1:(1-1.8). By adding water, the residual alkali on the surface of the material can be removed and the processing performance of the material can be improved.
[0051] The mass ratio of the secondary sintered product to the aluminum nitrate solution is 1:(2.012-2.024); for example, the mass ratio of the secondary sintered product to the aluminum nitrate solution can be 1:2.012, 1:2.015, 1:2.020, 1:2.024 or any value between 1:(2.012-2.024). The mass fraction of aluminum nitrate in the aluminum nitrate solution is 0.60%-1.19%. For example, the mass fraction of aluminum nitrate in the aluminum nitrate solution can be 0.60%, 0.70%, 0.80%, 0.90%, 1.00%, 1.10%, 1.19% or any value between 0.60%-1.19%.
[0052] According to an embodiment of the present application, the drying is carried out under vacuum conditions, and the drying temperature is 100-160°C; for example, the drying temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or any value between 100-160°C.
[0053] And / or, the drying time is 2-4 hours. For example, the drying time can be 2 hours, 3 hours, 4 hours or any value between 2-4 hours.
[0054] According to an embodiment of the present application, the doping element-containing additive includes boric acid; Furthermore, the additive containing doping elements also includes simple doping elements, oxides of doping elements, etc.
[0055] And / or, the mass of the doping element additive accounts for 0.05wt%-0.2wt% of the mass of the coated material; when the mass of the doping element additive is within the above range, the diffusion rate of lithium ions can be increased while making the material surface smoother and reducing the generation of microcracks, so that the positive electrode material has better rate performance. If the amount of the doping element additive added is too small, the purpose of significantly improving the material performance cannot be achieved; if the amount of the doping element additive added is too much, the risk of low capacity of the material will increase, the residual alkali on some surfaces will increase, and the electrochemical performance and processing performance will be affected.
[0056] For example, the mass of the doping element additive accounts for 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt% or any value between 0.05wt% and 0.2wt% of the mass of the coated material.
[0057] In some embodiments, the coated material and the additive containing the doping element are mixed in a high-speed mixer.
[0058] and / or, the sintering atmosphere of the third sintering includes oxygen; And / or, the heating rate of the three sinterings is 1-5°C / min; For example, the heating rate of the tertiary sintering may be 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, or any value between 1-5° C. / min.
[0059] And / or, the temperature of the three sintering is 200-400°C; for example, the temperature of the three sintering can be 200°C, 300°C, 400°C or any value between 200-400°C.
[0060] And / or, the time of the three sinterings is 9-12 hours. For example, the time of the three sinterings can be 9 hours, 10 hours, 11 hours, 12 hours or any value between 9-12 hours.
[0061] The present application also provides a ternary high-nickel positive electrode material, which is prepared by the preparation method of the ternary high-nickel positive electrode material described above.
[0062] The present application also provides a lithium-ion battery, which includes a ternary high-nickel positive electrode material prepared by the preparation method of the ternary high-nickel positive electrode material described above or includes the ternary high-nickel positive electrode material described above.
[0063] The present application also provides an electrical device, which includes the lithium-ion battery described above.
[0064] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0065] Example 1 Embodiment 1 provides a ternary high-nickel positive electrode material, and the preparation method thereof comprises: (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer according to the molar ratio of lithium to the total content of metal nickel, cobalt and manganese of 1:1.05. At the same time, nano zirconium oxide is added into the high-speed mixer, wherein the mass of nano zirconium oxide is Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor mass was 0.3wt%, and the high-speed mixer was rotated at a low speed of 270r / min for 5min and at a high speed of 500r / min for 20min to mix evenly.
[0066] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 750°C at a heating rate of 2°C / min, and a sintering is performed at 750°C for 13 hours to obtain a sintered material.
[0067] (3) The material obtained in step (2) is crushed using a mechanical crusher, wherein D50 is controlled between 8.5-9.5 μm.
[0068] (4) The material obtained in step (3) is taken out and put into a high-speed mixer. At the same time, 0.01 L of 99% tetrabutyl titanate is dissolved in 1 L of 80% ethanol to obtain a tetrabutyl titanate solution. The mass of the tetrabutyl titanate accounts for 0.1 wt% of the mass of the material after the first sintering. The tetrabutyl titanate solution is sprayed into the high-speed mixer during mixing, and the nozzle pressure is 0.05 MPa.
[0069] (5) The mixed material in step (4) is loaded into a sagger, the filling amount being 30% to 70% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen, the temperature is increased to 600° C. at a heating rate of 1° C. / min, and secondary sintering is performed at 600° C. for 11 hours to obtain a secondary sintered material.
[0070] (6) At 25°C, weigh 12g of aluminum nitrate and dissolve it in 1000g of pure water to obtain an aluminum nitrate solution. Take 500g of the material after secondary sintering in step (5), place it in a water washing kettle for water washing at a mass ratio of the secondary sintered material to pure water of 1:1.5, and add the prepared aluminum nitrate solution dropwise within 15 minutes to perform wet water washing and coating. After wet water washing and coating, centrifuge it and then place it in an oven for vacuum drying. The oven temperature is 120°C and the drying time is 2 hours to dry the material.
[0071] (7) Add the material obtained in step (6) and boric acid into a high-speed mixer, wherein the mass of the boric acid accounts for 0.1 wt % of the mass of the material obtained in step (6), and mix according to the mixing parameters of step (1).
[0072] (8) The material obtained in step (7) is loaded into a sagger, the filling amount being between 30% and 60% of the volume of the sagger, the material is placed in a box furnace, the temperature is raised to 300°C at a heating rate of 1°C / min, and sintered three times at 300°C for 11 hours to obtain a wet-coated ternary high-nickel positive electrode material.
[0073] Example 2 Embodiment 2 provides a ternary high nickel positive electrode material, and its preparation method comprises: (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer according to the molar ratio of lithium to the total content of metal nickel, cobalt and manganese of 1:1.05. At the same time, nano zirconium oxide is added into the high-speed mixer, wherein the mass of nano zirconium oxide is Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor mass was 0.3wt%, and the high-speed mixer was rotated at a low speed of 270r / min for 5min and at a high speed of 500r / min for 20min to mix evenly.
[0074] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 735°C at a heating rate of 2°C / min, and a sintering is performed once at 735°C for 13 hours to obtain a sintered material.
[0075] (3) The material obtained in step (2) is crushed using a mechanical crusher, wherein D50 is controlled between 8.5-9.5 μm. The SEM image of the crushed material is as follows: Figure 1 As shown by Figure 1 It can be seen that the average value of the primary particles in the material after one sintering is between 0.4 and 0.8 μm.
[0076] (4) The material obtained in step (3) is taken out and put into a high-speed mixer. At the same time, 0.03 L of 99% tetrabutyl titanate is dissolved in 1 L of 80% ethanol to obtain a tetrabutyl titanate solution. The mass of the tetrabutyl titanate accounts for 0.3 wt % of the mass of the material after the first sintering. The tetrabutyl titanate solution is sprayed into the high-speed mixer during mixing, and the nozzle pressure is 0.1 MPa.
[0077] (5) The mixed material in step (4) is loaded into a sagger, the filling amount being 30%-70% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 600°C at a heating rate of 1°C / min, and secondary sintering is performed at 600°C for 11 hours to obtain a secondary sintered material.
[0078] (6) At 25°C, weigh 8g of aluminum nitrate and dissolve it in 1000g of pure water to obtain an aluminum nitrate solution. Take 500g of the material after secondary sintering in step (5), and place it in a water washing kettle for water washing at a mass ratio of 1:1 between the secondary sintered material and pure water. At the same time, add 1000g of the prepared aluminum nitrate solution dropwise within 15 minutes to perform wet water washing and coating. After wet water washing and coating, centrifuge and place in an oven for vacuum drying. The oven temperature is 120°C and the drying time is 2 hours to dry the material. The SEM image of the dried material is as follows: Figure 2 , Figure 3 and Figure 4 As shown by Figure 2 , Figure 3 and Figure 4 The needle-shaped coating layer can be clearly seen and the coating material is evenly distributed.
[0079] (7) Add the material obtained in step (6) and boric acid into a high-speed mixer, wherein the mass of the boric acid accounts for 0.1 wt % of the mass of the material obtained in step (6), and mix according to the mixing parameters of step (1).
[0080] (8) The material obtained in step (7) is loaded into a sagger, the filling amount being between 30% and 60% of the volume of the sagger, the material is placed in a box furnace, the temperature is raised to 300°C at a heating rate of 1°C / min, and sintered three times at a temperature of 300°C. The three sintering times are 11 hours, and a wet-coated ternary high-nickel positive electrode material is obtained, the SEM image of which is shown in FIG. Figure 5 shown.
[0081] Comparative Example 1 (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer according to the molar ratio of lithium to the total content of metal nickel, cobalt and manganese of 1:1.05. At the same time, nano zirconium oxide is added into the high-speed mixer, wherein the mass of nano zirconium oxide is Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor mass was 0.3wt%, and the high-speed mixer was rotated at a low speed of 270r / min for 5min and at a high speed of 500r / min for 20min to mix evenly.
[0082] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 750°C at a heating rate of 2°C / min, and a sintering is performed at 750°C for 13 hours to obtain a sintered material.
[0083] (3) The material obtained in step (2) is crushed using a mechanical crusher, wherein D50 is controlled between 8.5-9.5 μm.
[0084] (4) The material obtained in step (3) is taken out and put into a high-speed mixer, and alumina and titanium dioxide are added at the same time, wherein the mass of alumina accounts for 0.1wt% of the mass of the material obtained in step (3), and the mass of titanium dioxide accounts for 0.12wt% of the mass of the material obtained in step (3). The materials are mixed according to the mixing process of step (1), and the dry-coated material is obtained after mixing.
[0085] (5) The mixed material in step (4) is loaded into a sagger, the filling amount being 30% to 70% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen, the temperature is increased to 600° C. at a heating rate of 1° C. / min, and secondary sintering is performed at 600° C. for 11 hours to obtain a secondary sintered material.
[0086] (6) The material in step (5) was washed with water for 15 minutes at a material:pure water mass ratio of 1:1.5, and centrifuged, and then vacuum dried in an oven at a temperature of 120°C for 2 hours to dry the material.
[0087] (7) Add the material obtained in step (6) and boric acid into a high-speed mixer, wherein the mass of the boric acid accounts for 0.1 wt % of the mass of the material obtained in step (6), and mix according to the mixing parameters of step (1).
[0088] (8) The material obtained in step (7) is loaded into a sagger, the filling amount being between 30% and 60% of the volume of the sagger, the material is placed in a box furnace, the temperature is increased to 300°C at a heating rate of 1°C / min, and sintered three times at a temperature of 300°C. The sintering time for the three times is 11 hours, and a dry-coated ternary high-nickel positive electrode material is obtained.
[0089] Comparative Example 2 (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer at a molar ratio of lithium to the total content of metallic nickel, cobalt and manganese of 1:1.05. The high-speed mixer rotates at a low speed of 270 r / min for 5 minutes and at a high speed of 500 r / min for 20 minutes to mix evenly.
[0090] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 750°C at a heating rate of 2°C / min, and a sintering is performed at 750°C for 13 hours.
[0091] (3) The primary sintered material obtained in step (2) is mechanically crushed to control the D50 of the material to be between 8.5 and 11.5 μm, thereby obtaining an uncoated and modified high-nickel ternary positive electrode material.
[0092] Comparative Example 3 (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer according to the molar ratio of lithium to the total content of metal nickel, cobalt and manganese of 1:1.05. At the same time, nano zirconium oxide is added into the high-speed mixer, wherein the mass of nano zirconium oxide is Ni 0.9 Co 0.06 Mn 0.04The (OH)2 precursor mass was 0.3wt%, and the high-speed mixer was rotated at a low speed of 270r / min for 5min and at a high speed of 500r / min for 20min to mix evenly.
[0093] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 750°C at a heating rate of 2°C / min, and a sintering is performed at 750°C for 13 hours to obtain a sintered material.
[0094] (3) The material obtained in step (2) is crushed using a mechanical crusher, wherein D50 is controlled between 8.5-9.5 μm.
[0095] (4) The material obtained in step (3) is taken out and put into a high-speed mixer. At the same time, 0.01 L of 99% tetrabutyl titanate is dissolved in 1 L of 80% ethanol to obtain a tetrabutyl titanate solution. The mass of the tetrabutyl titanate accounts for 0.1 wt% of the mass of the material after the first sintering. The tetrabutyl titanate solution is sprayed into the high-speed mixer during mixing, and the nozzle pressure is 0.05 MPa.
[0096] (5) The mixed material in step (4) is loaded into a sagger, the filling amount being 30% to 70% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen, the temperature is increased to 600° C. at a heating rate of 1° C. / min, and secondary sintering is performed at 600° C. for 11 hours to obtain a secondary sintered material.
[0097] (6) Take 500 g of the material after secondary sintering in step (5), wash it in a water washing kettle at a mass ratio of the material after secondary sintering to pure water of 1:1.5, centrifuge it after washing, and then place it in an oven for vacuum drying at a temperature of 120°C for 2 hours to dry the material.
[0098] (7) Add the material obtained in step (6) and boric acid into a high-speed mixer, wherein the mass of the boric acid accounts for 0.1 wt % of the mass of the material obtained in step (6), and mix according to the mixing parameters of step (1).
[0099] (8) The material obtained in step (7) is loaded into a sagger, the filling amount being between 30% and 60% of the volume of the sagger, the material is placed in a box furnace, the temperature is increased to 300°C at a heating rate of 1°C / min, and sintered three times at a temperature of 300°C. The sintering time for the three times is 11 hours, and a ternary high-nickel positive electrode material is obtained.
[0100] Comparative Example 4 (1) Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor and lithium hydroxide are put into a high-speed mixer according to the molar ratio of lithium to the total content of metal nickel, cobalt and manganese of 1:1.05. At the same time, nano zirconium oxide is added into the high-speed mixer, wherein the mass of nano zirconium oxide is Ni 0.9 Co 0.06 Mn 0.04 The (OH)2 precursor mass was 0.3wt%, and the high-speed mixer was rotated at a low speed of 270r / min for 5min and at a high speed of 500r / min for 20min to mix evenly.
[0101] (2) The mixed material in step (1) is loaded into a sagger, the filling amount being 50%-80% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen. The temperature is raised to 750°C at a heating rate of 2°C / min, and a sintering is performed at 750°C for 13 hours to obtain a sintered material.
[0102] (3) The material obtained in step (2) is crushed using a mechanical crusher, wherein D50 is controlled between 8.5-9.5 μm.
[0103] (4) The material obtained in step (3) is taken out and put into a high-speed mixer. At the same time, 0.01 L of 99% tetrabutyl titanate is dissolved in 1 L of 80% ethanol to obtain a tetrabutyl titanate solution. The mass of the tetrabutyl titanate accounts for 0.1 wt% of the mass of the material after the first sintering. The tetrabutyl titanate solution is sprayed into the high-speed mixer during mixing, and the nozzle pressure is 0.05 MPa.
[0104] (5) The mixed material in step (4) is loaded into a sagger, the filling amount being 30% to 70% of the sagger capacity, and the material is placed into a box furnace, wherein the sintering atmosphere is oxygen, the temperature is increased to 600° C. at a heating rate of 1° C. / min, and secondary sintering is performed at 600° C. for 11 hours to obtain a secondary sintered material.
[0105] (6) Add the material obtained in step (5) and boric acid into a high-speed mixer, wherein the mass of the boric acid accounts for 0.1 wt % of the mass of the material obtained in step (5), and mix according to the mixing parameters of step (1).
[0106] (7) The material obtained in step (6) is loaded into a sagger, the filling amount being between 30% and 60% of the volume of the sagger, the material is placed in a box furnace, the temperature is increased to 300°C at a heating rate of 1°C / min, and sintered three times at a temperature of 300°C. The sintering time for the three times is 11 hours, and a ternary high-nickel positive electrode material is obtained.
[0107] The positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-4 were assembled into lithium negative electrode button half-cells, and the electrochemical performance of the cells was tested under the following test conditions: 0.1C, 3.0-4.3V. The residual alkali content was also tested by titration using a 0.03 mol / L standard solution.
[0108] The test results of Examples 1-2 and Comparative Examples 1-4 are compared in Table 1.
[0109] Table 1 Comparison of test results of Examples 1-2 and Comparative Examples 1-4
[0110] It can be seen from Table 1 that Examples 1-2 can simultaneously have higher charge and discharge capacity and lower residual alkali content, and their comprehensive performance is significantly better than that of Comparative Examples 1-4.
[0111] Compared with Examples 1-2, Comparative Example 1 has lower charge capacity, discharge capacity, discharge efficiency and higher residual alkali content. This may be because the aluminum and titanium in Comparative Example 1 are introduced in a dry form, which has poor coating uniformity and consistency, resulting in poor electrochemical performance of the positive electrode material.
[0112] Compared with Examples 1-2, Comparative Example 2 has lower charge capacity, discharge capacity, discharge efficiency and higher residual alkali content. This may be due to the fact that Comparative Example 2 does not introduce zirconium-containing additives, titanium-containing additives, does not coat aluminum nitrate on the surface of the material, does not perform water washing, does not introduce additives containing doping elements, and other factors. These processing steps and the use of additives are crucial to improving the comprehensive performance of the positive electrode material, and their absence directly deteriorates the electrochemical performance of the positive electrode material of Comparative Example 2.
[0113] Compared with Examples 1-2, the charge capacity and discharge capacity of Comparative Example 3 are lower, which may be due to the fact that no aluminum nitrate solution is added in Comparative Example 3 and no aluminum nitrate coating layer is formed on the surface of the positive electrode material.
[0114] Compared with Examples 1-2, the charge capacity and discharge capacity of Comparative Example 4 are lower, and Comparative Example 3 has a higher residual alkali content, which may be due to the fact that Comparative Example 4 omits the water washing step and the step of adding aluminum nitrate solution.
[0115] Through the analysis of the above embodiments and comparative examples, it can be seen that the ternary positive electrode material modified by wet coating has better discharge capacity, lower residual alkali and more uniform coating layer.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0117] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a ternary high-nickel positive electrode material, characterized in that: include: The positive electrode material precursor, the lithium source and the zirconium-containing additive are mixed and sintered once to obtain a sintered product; The primary sintered product is mixed with a titanium-containing additive and subjected to secondary sintering to obtain a secondary sintered product; The secondary sintered product is mixed with water and aluminum nitrate, subjected to wet washing and coating, filtered, and dried to obtain a coated material; The coated material is mixed with an additive containing a doping element and sintered three times to obtain a ternary high-nickel positive electrode material, wherein the doping element includes at least one of B, Mg, Y, and Mo.
2. The method for preparing a ternary high-nickel cathode material according to claim 1, characterized in that: The positive electrode material precursor includes Ni x Co y Mn z (OH)2, where x≥0.9, y>0, z>0, x+y+z=1; And / or, the lithium source comprises lithium hydroxide; And / or, the molar ratio of lithium in the lithium source to the total content of nickel, cobalt and manganese in the positive electrode material precursor is 1:(1-2); and / or, the zirconium-containing additive comprises zirconium oxide; and / or, the mass of the zirconium-containing additive is 0.1wt%-0.3wt% of the mass of the positive electrode material precursor; and / or, the sintering atmosphere of the primary sintering includes oxygen; And / or, the heating rate of the primary sintering is 1-5°C / min; And / or, the primary sintering temperature is 700-1000°C; And / or, the time of the primary sintering is 12-14 hours.
3. The method for preparing a ternary high-nickel cathode material according to claim 1, characterized in that: The titanium-containing additive includes at least one of tetra-tert-butyl titanate, alkoxy titanate, and tetrabutyl titanate; and / or, the mass of the titanium-containing additive accounts for 0.1wt%-1wt% of the mass of the product after the primary sintering; and / or, the sintering atmosphere of the secondary sintering includes oxygen; And / or, the heating rate of the secondary sintering is 1-5°C / min; And / or, the secondary sintering temperature is 400-800°C; And / or, the secondary sintering time is 9-12 hours.
4. The method for preparing a ternary high-nickel cathode material according to claim 1, characterized in that: The mass of the aluminum nitrate accounts for 1.2wt%-2.4wt% of the mass of the product after the secondary sintering.
5. The method for preparing a ternary high-nickel cathode material according to claim 4, characterized in that: The mixing of the secondary sintered product with water and aluminum nitrate comprises: first mixing the secondary sintered product with water, and then adding aluminum nitrate solution; The mass ratio of the secondary sintered product to water is 1:(1-1.8); The mass ratio of the secondary sintered product to the aluminum nitrate solution is 1:(2.012-2.024); The mass fraction of aluminum nitrate in the aluminum nitrate solution is 0.60%-1.19%.
6. The method for preparing a ternary high-nickel cathode material according to claim 1, characterized in that: The drying is carried out under vacuum conditions at a temperature of 100-160°C; And / or, the drying time is 2-4 hours.
7. The method for preparing a ternary high-nickel cathode material according to any one of claims 1 to 6, characterized in that: Additives containing doping elements include boric acid; and / or, the mass of the additive containing the doping element accounts for 0.05wt%-0.2wt% of the mass of the coated material; and / or, the sintering atmosphere of the third sintering includes oxygen; And / or, the heating rate of the three sinterings is 1-5°C / min; And / or, the temperature of the three sinterings is 200-400°C; And / or, the time of the three sinterings is 9-12 hours.
8. A ternary high nickel positive electrode material, characterized in that: The ternary high-nickel positive electrode material is prepared by the preparation method of the ternary high-nickel positive electrode material according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the ternary high-nickel positive electrode material prepared by the method for preparing the ternary high-nickel positive electrode material according to any one of claims 1 to 7 or comprises the ternary high-nickel positive electrode material according to claim 8.
10. An electrical device, characterized in that: The electrical equipment comprises the lithium-ion battery according to claim 9.
Citation Information
Patent Citations
High nickel anode material, preparation method thereof and lithium ion battery
CN105070907A
Method for preparing high nickel anode material and lithium ion battery
CN105070908A
High-nickel single-crystal ternary cathode material with low surface residual alkali content and preparation method thereof
CN110436531A
Positive electrode material, preparation method thereof and lithium ion battery
CN111628157A
Ternary single crystal positive electrode material as well as preparation method and application thereof
CN112599763A
Cited By
Positive electrode material and preparation method thereof, positive plate and battery
CN121662775A